2023
DOI: 10.1177/09514848231165894
|View full text |Cite
|
Sign up to set email alerts
|

When caring breeds contempt: The impact of moral emotions on healthcare professionals’ commitment during a pandemic

Abstract: The novel coronavirus (COVID-19) pandemic is a major heath crisis that continues to impact healthcare organizations worldwide. As infection rates surged, there was a global shortage of personal protective equipment, critical medications, ventilators, and hospital beds, meaning that healthcare professionals faced increasingly difficult workplace conditions. In this conceptual study, we argue these situations can lead to healthcare professionals experiencing moral emotions - defined as specific emotions which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Similar to this study, it has been shown that staff shortage and the resulting demand to do mandatory overtime contributed to poor patient outcomes, burnout, increased stress, and compassion fatigue among nurses. [12,13,26,38,39] However, resilience and a sense of duty assisted in combating the dissatisfaction experienced, and an overall strong sense of kinship contributed to job satisfaction. Findings confirmed the need for so-called "after care" for nurses by leadership and administrators, which could come in the form of transparent and improved communication as well as new measures for ongoing support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to this study, it has been shown that staff shortage and the resulting demand to do mandatory overtime contributed to poor patient outcomes, burnout, increased stress, and compassion fatigue among nurses. [12,13,26,38,39] However, resilience and a sense of duty assisted in combating the dissatisfaction experienced, and an overall strong sense of kinship contributed to job satisfaction. Findings confirmed the need for so-called "after care" for nurses by leadership and administrators, which could come in the form of transparent and improved communication as well as new measures for ongoing support.…”
Section: Discussionmentioning
confidence: 99%
“…[24] The intense emotions nurses experience witnessing the effects of COVID-19 on patients, colleagues, and leadership ambiguity may lead to burnout and dissatisfaction with the profession; this may inspire RNs to leave nursing at a time when global nursing shortages are critical. [23,25,26] Little research pertains to the psychological influence of COVID-19 on Canadian RNs. To understand the psycho-logical influence of COVID-19 on RNs' self-efficacy and job satisfaction, we studied RNs living and working across Canada who had recently started graduate studies at an online university.…”
Section: Introductionmentioning
confidence: 99%